Carbaryl and Lindane Residues in and on Groundnut - Singh, K P; Pandey, S Y; Singh, S; Khan, M M; Galhotra, R (Annals of Arid Zone, 2016)
Field trials were conducted to study the magnitude of carbaryl and lindane residues in groundnut crop following application of carbaryl wettable powder and Sevidol granules @ 0.75 to 2.0 kg ai/ha. Samples of groundnut kernel, hull, foliage and soil were drawn at harvest. Carbaryl residues were estimated calorimetrically, whereas lindane by gas liquid chromatography. Carbaryl and lindane residues in groundnut kernel, hull, foliage and soil were below the respective tolerance limits.